2013
DOI: 10.1517/14728214.2013.831068
|View full text |Cite
|
Sign up to set email alerts
|

Emerging treatments for chronic constipation

Abstract: While undoubtedly effective, high-quality evidence to support laxatives, the traditional remedies for constipation, is remarkably scarce due, in large part, to the absence, until very recently, of high-quality randomized controlled clinical trials. The selective prokinetic agent prucalopride and the prosecretory agents lubiprostone and linaclotide have shown efficacy and been associated with a good safety record in large well-conducted clinical studies. Other novel approaches, such as the inhibition of ileal b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…[ 6 , 9 ] Few treatments have been shown to improve abdominal bloating in patients with CIC. [ 10 , 11 ] In fact, abdominal bloating may be exacerbated by some treatments aimed at improving constipation-related symptoms. [ 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 6 , 9 ] Few treatments have been shown to improve abdominal bloating in patients with CIC. [ 10 , 11 ] In fact, abdominal bloating may be exacerbated by some treatments aimed at improving constipation-related symptoms. [ 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…[ 10 , 11 ] In fact, abdominal bloating may be exacerbated by some treatments aimed at improving constipation-related symptoms. [ 10 , 11 ]…”
Section: Introductionmentioning
confidence: 99%
“…In such patients, mutations in CFTR result in downregulated transepithelial Clsecretion and are associated with the clinical manifestation of constipation and intestinal obstruction (van der Doef et al 2010). Furthermore, in non-CF patients with constipation, drugs which activate CFTR (e.g., lubiprostone) have been shown to be an effective treatment (Norimatsu et al 2012, Gudsoorkar andQuigley 2013).…”
Section: Cystic Fibrosis Transmembrane Conductance Regulatormentioning
confidence: 99%
“…Elobixibat is a potent inhibitor of ileal bile acid transporters. It therefore can increase the bile acid content in the colon which in turn increases the fluid secretion and motility of the colon 45 . One randomized, double-blind, placebo-controlled trial in adult females has shown some promising results including significant acceleration of colonic transit time 46 .…”
Section: Other Drugsmentioning
confidence: 99%